MENINGKATKAN PENGUASAAN VOCABULARIES SISWA MELALUI LAGU – LAGU BAHASA INGGRIS DI KELAS VIIl-2 SMP NEGERI 2 MARDINGDING SEMESTER GANJIL TAHUN PELAJARAN 2015/2016 - Br Sinulingga, Jendakita (ELT (English Language Teaching Prima Journal), 2021)
ABSTRACT This study aims to improve student learning outcomes in learning English by using the media of English songs. The subjects of this study were 27 students of class VIII-2 of SMP Negeri 2 Mardingding, Mardingding District, Karo Regency, consisting of 11 male students and 16 female students. The research method applied is a classroom action research method. Through two learning cycles, each cycle is carried out with planning, implementation, observation and reflection activities. Based on the results of data analysis, it is known that by using the media of English songs in English lessons in class VIII-2 of SMP Negeri 2 Mardingding, Mardingding District, Karo Regency, 2015/2016 Academic Year, mastery of students' vocabularies has increased from Cycle First to Cycle Second. Mastery of students' vocabularies in the first cycle obtained an average score of 30 with the percentage of the acquisition score of the total score of 30% and this is in the very poor category (not good). And far from KKM (70). In the second cycle of vocabulary mastery students obtained an average score of 80 with a percentage of the acquisition score of a total score of 80% and this is in a good category and has exceeded KKM (70). So, the increase in students' vocabularies mastery from cycle I to cycle II was 50%, while student learning outcomes after using English songs as media in learning English also increased. Likewise, the number of students who have completed the KKM has reached the indicators of success, where the standard is 80%, while the acquisition is 96%. Keywords: Using English songs improves mastery of English vocabularies